Identification and ranking of compensation strategies for oil distribution companies - Boudlaie, Hasan; Behrouz Keshavarz Nik; Mohammadhosein Kenarroodi (Technium Social Sciences Journal, 2020)
The purpose of the current study was to identify the strategic dimensions of sales force compensation in distribution companies. In this regard, three research questions have been answered: What are the appropriate strategies for employee compensation? What are the strategic dimensions of sales force compensation? What is the status of the study population regarding compensation? The study population consisted of sales managers in oil products distribution companies, academic professors in the field of marketing and sales at expert judgment department, 120 sales force and managers working in 20 oil products distribution companies. For statistical analysis, the Delphi method, analysis of means, binomial test and Friedman test were used. The results have shown that initially 16 strategies out of 40 proposed strategic reference points and then 17 approved strategic reference points in the sales force compensation section can be derived among which the following strategy held the top rating, “sales force compensation for services should be based on motivating factors in order to improve the competitive environment among employees and improve their sales performance”. Moreover, in terms of compensation strategy, the appropriateness of compensation for incentive service of sales force in the studied companies was at a favorite level.